Legal Protection of Intellectual Property Rights in the Digital Era - Riama Novalia Silaen; Tamaulina Br. Sembiring (Ipso Jure, 2024)
This research uses a qualitative approach with descriptive-analytical methods to examine the legal protection of intellectual property rights (HMI) in the digital era. The research results show that the legal protection of HMI in the digital era still faces various significant challenges. Even though regulations such as Law Number 28 of 2014 concerning Copyright and Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE) exist, their implementation could be more effective. The leading causes are a need for more public knowledge and awareness about the importance of HMI, as well as limited law enforcement resources and technology. Collaboration between the government and digital platforms needs to be improved, while international cooperation is also crucial in dealing with cross-border HMI violations. This research recommends increasing public education and awareness, strengthening regulations, adopting advanced technology such as AI, closer cooperation with digital platforms, increasing law enforcement capacity and resources, and efficient dispute resolution mechanisms. With a more holistic and integrated approach, HMI protection in the digital era can be significantly improved, providing justice for rights owners and encouraging the development of a healthier and more innovative creative industry.